2022
DOI: 10.1155/2022/2823314
|View full text |Cite|
|
Sign up to set email alerts
|

Surgical Treatment of Bilateral Chronic Subdural Hematoma

Abstract: Background. Chronic subdural hematoma (CSDH) is one of the common clinical intracranial hemorrhagic disorders, accounting for 16%–20% of bilateral CSDH. At present, the surgical treatment of bilateral CSDH mainly includes drilling drainage and neuroendoscopic assistance. The main objective of this paper was to compare the effects of two surgical methods on CSDH. Methods. 153 patients who were diagnosed with CSDH were included in this study. 79 patients were treated with bilateral drilling drainage, and the oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…CSH arises from the rupture and hemorrhage of veins subsequent to physical injury [ 8 ]. Venous hemorrhage has a gradual progression and typically ceases through the application of intracranial pressure or the formation of a clot.…”
Section: Discussionmentioning
confidence: 99%
“…CSH arises from the rupture and hemorrhage of veins subsequent to physical injury [ 8 ]. Venous hemorrhage has a gradual progression and typically ceases through the application of intracranial pressure or the formation of a clot.…”
Section: Discussionmentioning
confidence: 99%
“…Computational Intelligence and Neuroscience has retracted the article titled "Surgical Treatment of Bilateral Chronic Subdural Hematoma" [1] due to concerns that the peer review process has been compromised. Following an investigation conducted by the Hindawi Research Integrity team [2], signifcant concerns were identifed with the peer reviewers assigned to this article; the investigation has concluded that the peer review process was compromised.…”
mentioning
confidence: 99%
“…Computational Intelligence and Neuroscience has retracted the article titled “Surgical Treatment of Bilateral Chronic Subdural Hematoma” [ 1 ] due to concerns that the peer review process has been compromised.…”
mentioning
confidence: 99%